Suma crítica - YURKIEVICH, Saúl (FONDO DE CULTURA ECONOMICA, 1997)
Contiene:HUIDOBRO, Vicente; VALLEJO; NERUDA; GIRONDO; BORGES, Jorge Luis; CORTAZAR; PAZ, OCTAVIO; ONETTI; GARCIA MARQUEZ, Gabriel; LIMA, LEZAMA